Partisipasi Tokoh Masyarakat dalam Meningkatkan Pembangunan di Kelurahan Bangkai Kecamatan Watangpulu Kabupaten Sidenreng Rappang - Chandraleka Chandraleka (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2019)
Abstract This research was conducted at Bangkai Sub-district of Watangpulu District in Sidenreng Rappang Regency. The objectives: 1) to determine the role of community leaders in increasing participation in sub-district development, and 2) to determine the factors that affected the role of community leaders in improving participation in development proccess. Research methods were observation, interviews, providing a list of questions through a questionnaire, and literature study about the core of the problem in this research. The data was then analyzed using frequency tables and percentages. The population in this research took 997 of Bangkai Sub-district people. Samples taken using random sampling technique were some parts of the population, concluding twenty percent (20%) of the 997 heads of household to become 49.5, rounded to fifty (50) people. So, this research used a population sample. The data showed that the role of community leaders in improving participation in sub-district development was already optimized so that people's participation level were moderate with a score of 57%. The affecting factors that influence the participation of community leaders on sub-district development were high with 83% score.